Interventions and strategies involving primary healthcare professionals to manage emergency department overcrowding: a scoping review. Issue 5 (10th May 2021) - Jeyaraman, Maya M; Copstein, Leslie; Al-Yousif, Nameer; Alder, Rachel N; Kirkland, Scott W; Al-Yousif, Yahya; Suss, Roger; Zarychanski, Ryan; Doupe, Malcolm B; Berthelot, Simon; Mireault, Jean; Tardif, Patrick; et al.
Abstract : Objectives: To conduct a scoping review to identify and summarise the existing literature on interventions involving primary healthcare professionals to manage emergency department (ED) overcrowding. Design: A scoping review. Data sources: A comprehensive database search of Medline (Ovid), EMBASE (Ovid), Cochrane Library (Wiley) and CINAHL (EBSCO) databases was conducted (inception until January 2020) using peer-reviewed search strategies, complemented by a search of grey literature sources. Eligibility criteria: Interventions and strategies involving primary healthcare professionals (PHCPs: general practitioners (GPs), nurse practitioners (NPs) or nurses with expanded role) to manage ED overcrowding. Methods: We engaged and collaborated, with 13 patient partners during the design and conduct stages of this review. We conducted this review using the JBI guidelines. Two reviewers independently selected studies and extracted data. We conducted descriptive analysis of the included studies (frequencies and percentages). Results: From 23 947 records identified, we included 268 studies published between 1981 and 2020. The majority (58%) of studies were conducted in North America and were predominantly cohort studies (42%). The reported interventions were either 'within ED' (48%) interventions (eg, PHCP-led ED triage or fast track) or 'outside ED' interventions (52%) (eg, after-hours GP clinic and GP cooperatives). PHCPs involved in the interventions were: GP (32%), NP (26%), nurses with expanded role (16%) and combinations of the PHCPs (42%). The 'within ED' and 'outside ED' interventions reported outcomes on patient flow and ED utilisation, respectively. Conclusions: We identified many interventions involving PHCPs that predominantly reported a positive impact on ED utilisation/patient flow metrics. Future research needs to focus on conducting well-designed randomized controlled trials (RCTs) and systematic reviews to evaluate the effectiveness of specific interventions involving PHCPs to critically appraise and summarise evidence on this topic.